ECONOMIC EFFICIENCY MANAGEMENT MECHANISM OF MARKETING ACTIVITIES IN INDUSTRIAL ENTERPRISES (International journal of artificial intelligence, 2026)
this article will talk about the unified system of production, supply, logistics, price Policy, Advertising and Consumer Relations of marketing activities in industrial enterprises.